Correlation between the histopathology of chronic urticaria and its clinical picture - Marques,Raquel Zappa Silva (2016)
Abstract BACKGROUND: Chronic urticaria is characterized by transient, pruritic lesions of varying sizes, with central pallor and well-defined edges, with disease duration longer than six weeks. Its cellular infiltrate consists of neutrophils, lymphocytes and eosinophils. There is a subgroup of patients with eosinophilic or neutrophilic urticaria, resistant to the treatment with antihistamines, but that respond to a combination of antihistamine with other drugs. OBJECTIVE: To evaluate the present infiltration in chronic urticaria biopsies and correlate it with the clinical disease activity and response to treatment. METHODS: Forty-one patients with chronic urticaria were classified according to the score of severity of the disease, response to treatment and type of perivascular infiltrate. Inflammatory infiltrates were divided in eosinophilic (46.30%), neutrophilic and mixed. RESULTS: An association was found between the eosinophilic infiltrate and clinical scores of greater severity (p = 0.002). CONCLUSION: This association shows that the eosinophilic inflammatory infiltrates denote high clinical activity, which means more severe and exuberant clinical pictures of the disease.